Takaful and retakaful: advanced principles and practices - Frenz, Tobias; Soualhi, Younes (Islamic Banking and Finance Institut Malaysia (IBFIM), 2010)
This publication is based on the research done in the course of setting up Munich Re’s office for Islamic reinsurance: Munich Re’s retakaful operation (MRR) was licensed by the Central Bank of Malaysia on 31 December 2007 in Kuala Lumpur to conduct worldwide family and general retakaful business. The purpose of this publication is to provide an insight into the principles and current practices of Islamic insurance (takaful) and reinsurance (retakaful) for takaful practitioners and scholars of Islamic law (Shari’a) as well as readers new to Islamic insurance, It provides a balanced mix of general background information, technical knowledge and examples from the current key takaful markets, written by two experts in the field, one a German actuary and the other a Shari’a Scholar. The publication will equip the reader with a detailed knowledge of takaful, complemented by a primer on the Islamic banking and capital market as well as Islamic contract law. This publication will be updated regularly to reflect the fast pace at which the takaful and retakaful industry is developing. It does not aim to be comprehensive and exhaustive, but a rather a snapshot of the current practices and discussions within the takaful industry. At Munich Re we are convinced that there is ample space for innovation and optimisation in the takaful industry and hope that this publication will give food for thought and contribute ideas for further development.